MEMBANGUN KETERAMPILAN SOSIAL BAGI ANAK EKSTROVERT DI SEKOLAH DASAR - Hasanah, Saidah; Alpian, Yayan; Prawiyogi, Anggy Giri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine social skills for extroverted children in elementary school. This research method uses qualitative methods with the type of case study research (case study) and is descriptive with data techniques including observation, interviews, and documentation. Every child has a unique personality, and one of the personality types that is often encountered is extroverted. Children who have extroverted traits often experience problems in situations that require calm and concentration, for example when studying alone, these students may have a tendency to always seek attention, sometimes become bored with monotonous activities, and find it difficult to control themselves. It is important to provide opportunities for a person to interact with others socially. However, the child is lacking in the area of social skills, such as talking too much and being insensitive to the feelings of people around him who feel disturbed. With the existence of social skills, students can bring out an ability related to social so that they can achieve various achievements from these students.